Uji Toksisitas Akut Limbah Cair Electroplating Industri X Serta Serapan Logam Cr, Cu, Dan Ni (BCF) Terhadap Ikan Baung (Hemibagrus sp) Dengan Metode Static Test - Khairegtah, Said M. Fitra; Elystia, Shinta; Priyambada, Gunadi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Electroplating activities produce small quantities of waste water but the level of toxicity is very dangerous because it contains heavy metals. Chemical parameters measured in this reasearch are Cr (total), Cu, and Ni. The measurement results showed the levels of chemical parameters generally exceeded the quality standard. It is necessary to do an acute toxicity test and bioconcentration factor (BCF) which is one way to monitor the negative impacts of electroplating waste water. This research was using electroplating X wastewater in Pekanbaru City and research aims are determine the LC50 value, TUa value and analyze the relationship between the quality of electroplating X waste water and its toxicity level which is supported by data on the absorption of pollutant metals in the body of test animals (BCF). An acute toxicity test was done by static method within 96 hours using a test animal of baung fish (Hemibagrus sp). The death of baung fish (Hemibagrus sp) was analyzed using the probit method. The LC50 test results were 4,8% and the TUa value was 20,833 with category III namely the level of High Acute Toxicity and BCF values of Cr (total), Cu and Ni were 0,046; 0,000102; 0,00527 with the category of low accumulation value (BCF <1). Keywords: Acute Toxicity Test, Electroplating Waste Water, Baung Fish (Hemibagrus sp), LC50, BCF.